Clinical Spectra of Psoriatic Arthritis Interfacing Psoriatic Patients - Siddique, Mohammad Rahmat Ullah; Rashid, Muhammad Munir; Wahab, Md Abdul; Khondker, Lubna; Uddin, Mohammad Jamal; Shamim, Sarker Mahbub Ahmed; Islam, Md Zafrul; Al-Mamun, Abdullah (Community Based Medical Journal, 2013)
DOI: http://dx.doi.org/10.3329/cbmj.v1i2.13860 Community Based Medical Journal Vol.1(2) 2012 26-31